Koliminalidad the Laguna community mental health center - Soriano, Seichi Rens C. (College of Architecture, University of the Philippines Diliman, 2019)
With the newky signed Mental Health Act and the current surge in mental health awareness, the Philippines now has the opportunity to improve its mental health system. The approach towards community-based mental health is being considered and favored, however, it could be argued that this approach should be aiming towards transformative change, rather than just curative change. The thesis aims to design an integrated community-based center for different levels of mental health that benefits both the mentally ill and the general public that supports mental healing and development of well-being through an immersive community setting, rehabilitative and transitional experience, and stress-free environment. In mental health design, the problem is not the patient or their families, the problem lies in the community, and new approaches should be considered towards transforming the public to be more accepting so that the mentally ill can feel more inclusive in going back to that community while recovering.